2016
DOI: 10.1080/10942912.2015.1126722
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Bunium persicum and Rosmarinus officinalis Essential Oils and Their Synergy with Citric Acid on the Oxidation of Virgin Olive Oil

Abstract: The objective of this study was to evaluate the effect of Bunium persicum and Rosmarinus officinalis essential oils on the oxidation of virgin olive oil during accelerated storage. The synergistic effect between citric acid and antioxidants of natural and synthetic types was investigated. The B. persicum and R. officinalis essential oils significantly retarded the oxidation of virgin olive oil. Their antioxidant capacity was comparable to butylatedhydroxytoluene and better than β-carotene. Here we show that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…[15] This indicates the existence of synergetic or antagonistic effects due to the complex multicomponent composition of the oils. [31][32][33] The in vitro antimicrobial activity of M. pulegium, M. requenii, and M. aquatica aerial parts of EOs was assayed against 13 bacterial and five yeast species. Table 4 shows the MIC of the different strains tested.…”
Section: Resultsmentioning
confidence: 99%
“…[15] This indicates the existence of synergetic or antagonistic effects due to the complex multicomponent composition of the oils. [31][32][33] The in vitro antimicrobial activity of M. pulegium, M. requenii, and M. aquatica aerial parts of EOs was assayed against 13 bacterial and five yeast species. Table 4 shows the MIC of the different strains tested.…”
Section: Resultsmentioning
confidence: 99%
“…was used. Fatty acid methyl esters of linseed oil were prepared according to the method described by Keramat et al …”
Section: Methodsmentioning
confidence: 99%
“…Similar to PV results, the differences between inhibitory effects of β-carotene and BHT were more obvious at the latter stages of oxidation. Similarly, Keramat, Golmakani, Aminlari, & Shekarforoush (2016) reported that β-carotene reduced the oxidation of virgin olive oil to the same extent as BHT did after 21 days of storage, while BHT was found to be more effective than β-carotene after 42 days.…”
Section: Pv Av and Tvmentioning
confidence: 99%